2018
DOI: 10.1007/s00784-018-2513-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two disinfection/sterilization methods for dentin specimens on dentin permeability

Abstract: Considering the influences of dentin permeability by disinfection/sterilization methods, the disinfection of the acid-etched dentin disks using 70% ethanol for 15 min could be used for the study related to dentin permeability, while the sterilization of autoclaving could not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…In the present study, both steam autoclaving and gamma radiation negatively affected the PBS values of the human and bovine dentin posts. Jiang et al found that autoclaving caused collagen denaturation and coagulation resulting decreased dentin permeability (21). On the contrary, White et al found that gamma radiation had no effect on dentin permeability or structure; however, they reported that autoclave sterilization induced a loss of mineral and collagen components from the surface, with a change in the mineral component (13).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both steam autoclaving and gamma radiation negatively affected the PBS values of the human and bovine dentin posts. Jiang et al found that autoclaving caused collagen denaturation and coagulation resulting decreased dentin permeability (21). On the contrary, White et al found that gamma radiation had no effect on dentin permeability or structure; however, they reported that autoclave sterilization induced a loss of mineral and collagen components from the surface, with a change in the mineral component (13).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to create a sound connection with the bonding material is widely described and studied in terms of permeability of the dentin. [31][32][33] Although Pashley et al 32 did not report any adverse effects of autoclave sterilization, another study 33 using a modified method led to the opposite conclusion. Before sterilization, the teeth were etched with 35% orthophosphoric acid.…”
Section: Autoclavementioning
confidence: 99%
“…Before sterilization, the teeth were etched with 35% orthophosphoric acid. 33 That procedure removed the smear layer and partially demineralized the intertubu-lar dentin. The organic components responsible for creating a hybrid layer (collagen network) were exposed.…”
Section: Autoclavementioning
confidence: 99%
See 1 more Smart Citation
“…Despite their effectiveness, both methods are associated with disadvantages. While autoclaving has been shown to adversely affect dentinal structure, including dentin permeability [ 8 , 9 , 10 ], formalin is a known cytotoxic and genotoxic agent [ 11 ]. Acute exposure to formalin can result in severe skin, eye, and respiratory tract irritation, while chronic exposure is associated with nasopharyngeal cancer and myeloid leukemia [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%